Association of Overweight and Inflammatory Indicators with Breast Cancer: A Cross-Sectional Study in Chinese Women - Zha JM; Zhang M; Wang T; Li HS; Ban QY; Liu M; Jiang XX; Guo SY; Wang J; Zhou YR; Liu YH; He WQ; et al. (Dove Medical Press, 2024)
Juan-Min Zha,1,* Mei Zhang,1,* Tao Wang,2,* Hua-Shan Li,1,2,* Quan-Yao Ban,1,* Mei Liu,1 Xue-Xue Jiang,1 Shi-Ying Guo,2 Jing Wang,2 Ya-Ru Zhou,2 Yu-Hong Liu,2 Wei-Qi He,1,2 Hong Xu1 1Department of Oncology, the First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, 215006, People's Republic of China; 2Jiangsu Key Laboratory of Neuropsychiatric Diseases and Cambridge-Suda (CAM-SU) Genomic Resource Center, Medical College of Soochow University, Suzhou, Jiangsu, People's Republic of China*These authors contributed equally to this workCorrespondence: Wei-Qi He; Hong Xu, Department of Oncology, the First Affiliated Hospital of Soochow University, Suzhou, Jiangsu, 215006, People's Republic of China, Tel +86-512-6588-3545, Email whe@suda.edu.cn; hongxusuda@outlook.comObjective: This cross-sectional study aimed to explore the association of overweight and inflammatory indicators with breast cancer risk in Chinese patients.Methods: Weight, height, and peripheral blood inflammatory indicators, including white blood cell count (WBC), neutrophil count (NE), lymphocyte count (LY), platelet count (PLT) and the concentration of hypersensitivity C-reactive protein (hsCRP), were collected in 383 patients with benign breast lumps (non-cancer) and 358 patients with malignant breast tumors (cancer) at the First Affiliated Hospital of Soochow University, China, from March 2018 to July 2020. Body mass index (BMI), neutrophil-lymphocyte ratio (NLR), platelet-lymphocyte ratio (PLR) and systemic immune-inflammation index (SII) were determined according to the ratio equation. The correlations among overweight, inflammatory indicators, and the proportion of non-cancer or cancer cases were analyzed.Results: BMI is associated with an increased breast cancer risk. Compared with non-cancer patients, the average WBC count, NE count, NLR, and level of hsCRP were significantly higher in cancer patients. The level of hsCRP was closely associated with the size of malignant breast tumors.Conclusion: We conclude that overweight and high levels of hsCRP may serve as putative risk factors for malignant breast tumors in Chinese women.Keywords: breast cancer, body mass index, overweight, chronic inflammation, inflammatory indicator